Suspected immune checkpoint inhibitor‐induced pulmonary sarcoid reaction in metastatic renal cell carcinoma. Issue 7 (11th July 2022) - Purcell, Victoria; Preti, Beatrice; Fernandes, Ricardo
Abstract: We present the case of a 50‐year‐old male patient with metastatic clear cell renal cell carcinoma (mRCC) who developed a diffuse pulmonary opacification and lymphadenopathy during nivolumab maintenance therapy. This was diagnosed as presumed sarcoid granulomatous inflammatory reaction secondary to immunotherapy, which resolved with holding off therapy and the nivolumab was resumed. Abstract : We report a unique case of an immunotherapy‐induced sarcoid‐like reaction in the treatment of metastatic renal cell carcinoma. It is imperative that clinicians are aware these reactions often phenotypically resemble metastasis or disease progression and it may otherwise result in an unwarranted interruption of cancer treatment.